Forces Affecting the Interindustry Wage Structure - Ross, Arthur M.; Goldner, William (Quarterly Journal of Economics, 1950)
I. Introduction, 254. — II. Recent research on the interindustry wage structure, 255. — III. The original level of earnings, 257. — IV. Degree of organization, 266. — V. Changes in employment, 269. — VI. Other influences, 277. — VII. Conclusions, 278.